2019
DOI: 10.3389/fimmu.2019.00854
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Induces Immunoregulation of TREG, M2, and pDCs in a Lung Allergic Inflammation Model

Abstract: The benefits of moderate aerobic physical exercise for allergic asthma are well-known, particularly that of the anti-inflammatory effect that occurs by reducing Th2 responses and lung remodeling. However, the mechanisms of this immunoregulation are still under investigation. In this study, we investigated the possible immunoregulatory mechanisms of lung inflammation induced by moderate aerobic exercise in an experimental asthma model. BALB/c mice were distributed into Control, Exercise (EX), OVA, and OEX group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
(30 reference statements)
0
18
0
1
Order By: Relevance
“…In sarcoidosis, the exaggerated inflammatory response has, at least partly, been explained by a dampened function and/ or reduced frequency in BALF and blood of T regs . Interestingly, in a mice model of asthma, physical exercise caused an increase of activated T regs in the lungs [37]. Thus, a possible explanation for the positive effect of training could be restoration of a dysregulated T reg pool.…”
Section: Discussionmentioning
confidence: 99%
“…In sarcoidosis, the exaggerated inflammatory response has, at least partly, been explained by a dampened function and/ or reduced frequency in BALF and blood of T regs . Interestingly, in a mice model of asthma, physical exercise caused an increase of activated T regs in the lungs [37]. Thus, a possible explanation for the positive effect of training could be restoration of a dysregulated T reg pool.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory response induced by regular PA is mediated by skeletal muscle contraction through the release of muscle-derived cytokines (myokines). Moderate PA induces a marked increase in serum levels of cytokines involved in the regulation of inflammation, such as IL-10, IL-1 receptor antagonist (IL-1ra), and IL-37 (Pedersen and Febbraio 2008 ; Fernandes et al 2019 ; Abbasi et al 2014 ; Nold et al 2010 ). On the other hand, another myokine, IL-6, acts in suppressing the secretion of pro-inflammatory cytokines in several tissues, contributing to the creation of an anti-inflammatory environment for several hours after exercise.…”
Section: Impact Of Physical Exercise On Organs’ Response To Viral Infmentioning
confidence: 99%
“…The mechanisms of how exercise exerts its anti-inflammatory effects in this simplified mouse model of asthma remain unclear, although reduced NF-κB activation [23], increases in glucocorticoid receptor expression [24], FoxP3 increases [27], T-cell trafficking in response to an allergen challenge [30] with increased lung recruitment of Tregs and macrophages [33], and increased IL-10 and IL-1ra have been proposed [25,21], with IL-10 increases recently directly linked with increases in M2 macrophages in the lung tissue [33].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Alterations in airway epithelium are important in inflammation and airway remodelling in asthma. VIEIRA et al [33] investigated the effects of aerobic exercise on airway epithelial cells in OVA-sensitised mice and showed that low-intensity aerobic exercise reduced oxidative and nitrosative stress. There was reduced epithelial expression of NF-κB and P2X7R (a plasma membrane receptor involved in control of proinflammatory cytokine expression) and increased expression of epithelial IL-10.…”
Section: Animal Studiesmentioning
confidence: 99%